2021
DOI: 10.1038/s41598-021-94498-6
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the oral microbiome are associated with depression in young adults

Abstract: A growing body of evidence supports an important role for alterations in the brain-gut-microbiome axis in the aetiology of depression and other psychiatric disorders. The potential role of the oral microbiome in mental health has received little attention, even though it is one of the most diverse microbiomes in the body and oral dysbiosis has been linked to systemic diseases with an underlying inflammatory aetiology. This study examines the structure and composition of the salivary microbiome for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 51 publications
4
48
0
Order By: Relevance
“… 281 In a depression-related study, 1S rRNA gene-based next-generation sequencing was used to profile the bacterial composition of saliva in depressed patients compared with young adults; it has shown diversification but importantly, increased Prevotella nigrescens and Neisseria was observed in depressed individuals. 282 Smoking and alcohol consumption are two major factors that induce dysbiosis in oral microbiota and promote growth of pathogenic bacteria. 280 A meta-analysis study has revealed that drinking alcohol is associated with pathogenesis of AD and also with significantly decreased level in Firmicutes phyla and an increased level in Bacteroides phyla in these patients.…”
Section: Microbiota In the Development Of Diseasesmentioning
confidence: 99%
“… 281 In a depression-related study, 1S rRNA gene-based next-generation sequencing was used to profile the bacterial composition of saliva in depressed patients compared with young adults; it has shown diversification but importantly, increased Prevotella nigrescens and Neisseria was observed in depressed individuals. 282 Smoking and alcohol consumption are two major factors that induce dysbiosis in oral microbiota and promote growth of pathogenic bacteria. 280 A meta-analysis study has revealed that drinking alcohol is associated with pathogenesis of AD and also with significantly decreased level in Firmicutes phyla and an increased level in Bacteroides phyla in these patients.…”
Section: Microbiota In the Development Of Diseasesmentioning
confidence: 99%
“…Wingfield et al compared the salivary microbiome of adolescents with MDD and HCs and found that a total of 21 taxa of bacteria were more abundant and 19 others were less abundant in MDD patients. The most abundant genera in the patient group were Prevotella nirescens and Neisseria [99]. Another study focused on the diversity of bacterial taxa, but the results showed that the composition, rather than diversity, mattered when associating with depression or anxiety symptoms in young adults.…”
Section: Gi Biomarkers and Pediatric Depressive Disordermentioning
confidence: 99%
“…( 102 ), suggesting that oral microbiome composition can be associated with adolescent anxiety and depression symptoms. In addition, Wingfield et al ( 103 ), detecting the structure and composition of the salivary microbiome in young MDD adults as compared with control subjects, evidenced that a total of 21 bacterial taxa were differentially abundant in the depressed cohort, including increased Neisseria spp. and Prevotella nigrescens , while 19 taxa had a decreased abundance.…”
Section: Introductionmentioning
confidence: 99%